Chess as a Tool to Enhance Learning in Early Childhood Education in South African Rural Primary Schools - Ntandokamenzi Penelope Dlamini (Indonesian Journal of Early Childhood Education Studies, 2025)
Innovative strategies are urgently needed to improve learning and engagement in resource-constrained rural South African classrooms. Despite the potential of non-traditional tools, little research has investigated how chess can support early childhood education in these contexts. This study addresses this gap by exploring how chess, through the Tsogo Sun Moves for Life (M4L) programme, affects learning, participation, and behaviour in early childhood classrooms. A qualitative research design was employed, with data collected through semi-structured interviews with sixteen participants, including teachers, an education district official, and the chess program coordinator. The data were analysed thematically to identify patterns in experiences and perceptions. Findings indicate that chess enhances learner motivation, concentration, and active participation, while promoting social skills such as teamwork, patience, and resilience. Participants reported that chess transformed classrooms into inclusive and dynamic learning environments. This study demonstrates that chess is a low-cost, practical strategy for supporting holistic learner development in rural schools. By highlighting the educational benefits of chess, this research contributes to the knowledge base on inclusive pedagogy and curriculum innovation in early childhood education.